EKSISTENSI LINGGA SEBAGAI MEDIA PEMUJAAN HINDU DI DESA LINGGOASRI, KECAMATAN KAJEN, KABUPATEN PEKALONGAN - JAWA TENGAH (SEBUAH TINJAUAN PERSPEKTIF SEJARAH) - Suhardi, Untung (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2019)
Linga as a type of worship that exists in Hinduism which has begun to be abandoned by followers because it is ancient. The problems presented were about the history of the worship of the phallus and the form of the functions and meaning of the worship of the phallus in the village of Linggoasri, Pekalongan Regency, Central Java. The method uses descriptive analysis with a historical approach. The results of his research are other historical objects that resemble the phallus pair is yoni so, the existence of the phallus and yoni is interpreted as the embodiment of male and female symbols. The phallus worship ritual has the form that the phallus in Linggoasri concluded that the phallus is a phallus shaped with a rectangular base (brahma bhaga), with the longer end (the swastika phallus) and the upper part shaped ardhacandrakara (half-moon shaped) . Furthermore, the worship of the phallus is a symbol that has an ancient worship that illustrates fertility and well-being.